Richir, Merleau Ponty, and the possibility of a transcendental aesthetics - Piazza, Anna (Logos. Anales del Seminario de Metafísica, 2025)
This article exposes Marc Richir’s grounding of a transcendental aesthetics and his understanding of art, which considers the idea, already investigated by Husserl, that imagination and phantasy are fundamental pre-intentional acts that delineate the horizons of the relationship of human and world, both affectively and epistemologically. It has been studied how Richir’s phenomenological perspective was influenced on the one hand by Edmund Husserl’s analysis of specific acts of consciousness, and, on the other hand, by Kant’s transcendental schematism. However, in my article I show how Richir’s perspective on a transcendental aesthetics is particularly fertile because it incorporates, not only Kant’s schematism and Husserl’s Aktanalyse, but also Merleau-Ponty’s idea of a “flesh of the world” and his contribution to the understanding of the affective, bodily nature of knowledge, which, as it will be exposed, offers a new account of the transcendental. This sheds a light not only on specific epistemological matters, but also on the fact of art itself.